Pengaruh Inovasi Produk Terhadap Keberhasilan Usaha Kecil Dan Menengah (UKM) Kuliner Di Kota Tangerang Selatan - Muhammad Rizki Armanda; Iva Khoiril Mala (International Forum of Researchers and Lecturers, 2024)
The success of small and medium-sized enterprises (SMEs) in facing increasingly fierce market competition is highly dependent on product innovation. This study aims to find the types of product innovation applied and used by SMEs, analyze how product innovation affects the success of SMEs, and find factors that support and hinder the implementation of product innovation. This research method uses qualitative with data collection techniques through observation and interviews. The results showed that product innovation includes creating new products, improving product quality, product diversification and several factors through the 4Ps support innovation such as product, price, place, and promotion.